Metaplastic Breast Carcinoma: A Rare Entity - Shrestha, Roshani; Neupane, Prakash Raj; Satyal, Bandana (Nepalese Journal of Cancer, 2019)
Metaplastic Breast Carcinoma is a rare malignancy among invasive breast carcinoma. The patients usually present with large tumor size, axillary lymphnode metastasis and triple negative. The management of Metaplastic Breast carcinoma largely parallels that of Invasive Breast Carcinoma. In this case report, we found a case of metaplastic breast carcinoma with axillary lymphnode metastasis which is very rare.